Sistem Pendukung Keputusan Penerimaan Pegawai Baru menggunakan Metode AHP dan TOPSIS - Muhamad Fahrur Rozi; Edy Santoso; Muhammad Tanzil Furqon (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Employees as individuals who provide expertise for companies and organizations that require worker services in an effort to achieve the needs of human resources as a plan and efforts to complete the needs of the workforce so that competent selection to get the quality and progress of the company. In this study aims to provide employee selection recommendations using the implementation of Analytic Hierarchy Proces (AHP) and Technique for Order Preference by Similarity (TOPSIS) methods which will consider the criteria used as employee selection at PT Jagaraga Adika, Surabaya by using four criteria as considerations for new recruitment selection, including initial selection, psychologist test, security training, and interview. The results of the implementation of the AHP-TOPSIS method on employee recommendations are in the form of ranking the best employees obtained from the assessment criteria used, where the data used amounted to 638 data from January to December. The system that has been built shows the best accuracy results reaching 100% in the February and June period, while the lowest results obtained by the system are 82.50% in March and with an average best accuracy reaches 91.23%.